Interacting with Photons: Creating Interactive Projected Augmented Reality Experiences - Benko, Hrvoje (2015)
Interacting with Photons: Creating Interactive Projected Augmented Reality Experiences Slideshow
TUX Sander's Distinghished Speaker Series in Toronto, ON on October 13, 2015 Columbia University on October 14, 2015 New York University on October 15, 2015